PROFIL PENGGUNAAN ALAT KB PADA PASANGAN USIA SUBUR DI WILAYAH KERJA PUSKESMAS KAMANG TAHUN 2022 - Nengsih, Widya; Mardiah, Ainal; Mulyani, Citra (Universitas Fort de Kock Bukittinggi, 2023)
The population growth rate continues to rise annually, with the count reaching 271,066,366 individuals in 2020 and escalating further to 273,879,750 people in 2021. Government initiatives to manage this growth involve reducing birth rates through family planning programs. Active in 2021, Kamang KB Community Health Center attended to 2,728 out of 4,534 Potential Couples of Reproductive Age (PUS). This study aims to delineate the profile of family planning acceptors within the operational domain of Kamang Community Health Center in 2022. Employing a descriptive design, the research transpired in March - April 2023. The study population includes all family planning acceptors within Kamang Community Health Center's operational region, amounting to 2,728 individuals. By employing the Slovin formula, the sample size was determined as 348 people using the Incidental Sampling technique. Univariate analysis is applied for data analysis. The results reveal that within the health center's operational domain, family planning acceptors comprise 56% of individuals in the reproductive age group. Moreover, 76.7% of them are multipara, 81.89% are not engaged in employment, 74.13% belong to a higher socioeconomic stratum, and 71.8% employ injectable contraception. Other methods include pill contraception (7.5%), condom usage (8.6%), intrauterine device (IUD) usage (0.57%), implant usage (7.18%), and natural methods (4.3%). The majority (75.9%) reported no side effects, while 30.46% experienced them. Furthermore, 99.4% received support from their husbands. In conclusion, this study indicates that factors like age, parity, occupation, socio-economic status, side effects, and husband's support do not significantly influence contraceptive choices. It is recommended that mothers enhance their understanding of family planning to bolster motivation and foster greater interest in its adoption. Keywords : Contraception, Parity, Socioeconomic, Contraception History, Husband's Support